2022
DOI: 10.1186/s11658-022-00342-8
|View full text |Cite
|
Sign up to set email alerts
|

METTL16 promotes hepatocellular carcinoma progression through downregulating RAB11B-AS1 in an m6A-dependent manner

Abstract: Background The molecular mechanisms driving hepatocellular carcinoma (HCC) remain largely unclear. As one of the major epitranscriptomic modifications, N6-methyladenosine (m6A) plays key roles in HCC. The aim of this study was to investigate the expression, roles, and mechanisms of action of the RNA methyltransferase methyltransferase-like protein 16 (METTL16) in HCC. Methods The expression of METTL16 and RAB11B-AS1 was determined by RT-qPCR. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Moreover, the depletion of METTL16 inhibits gastric cancer (GC) and hepatocellular carcinoma (HCC) 51 . In accordance with this, high METTL16 expression has been linked with poor survival in the case of GC 52 and prognosis in the case of HCC 53 . It has been also shown that METTL16 binds to the metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) lncRNA 6 .…”
Section: Introductionsupporting
confidence: 60%
“…Moreover, the depletion of METTL16 inhibits gastric cancer (GC) and hepatocellular carcinoma (HCC) 51 . In accordance with this, high METTL16 expression has been linked with poor survival in the case of GC 52 and prognosis in the case of HCC 53 . It has been also shown that METTL16 binds to the metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) lncRNA 6 .…”
Section: Introductionsupporting
confidence: 60%
“…In gastric cancer, researchers found that METTL16 is highly expressed in cancer tissues, and METTL16-mediated m6A methylation promotes GC cell proliferation by enhancing cyclin D1 expression ( 35 ). The regulatory effects of METTL16 on malignant tumors ( 16 ) such as breast cancer ( 36 ) and liver cancer ( 37 ) have also been reported. However, in our study, we revealed for the first time that the novel m6A writer METTL16 was significantly decreased in PC cells and played a tumor suppressor role during human pancreatic carcinogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the central role of methyltransferase like proteins METTL1, METTL3, METTL6, METTL16, and METTL18 in regulating aberrant expression in human hepatocellular carcinoma tissues and pathogenesis and progression of HCC cells, such as cell survival, proliferation, metastasis, and invasion which in turns makes them novel biomarkers [11][12][13][14][15][16][17]. However, despite identifying a few multi-kinases or receptors targeting anti-cancer inhibitors, no multi-target drugs or inhibitors have been reported against HCC-associated METTL proteins [68].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, METTL16 is another identified m6A methyltransferase, which negatively correlated with decreased RAB11B-AS1 transcript expression in HCC tissues. Thus, the METTL16–RAB11B-AS1 regulatory axis and these above-mentioned methyltransferase family proteins become novel biomarkers and therapeutic targets for hepatocellular carcinoma [17].…”
Section: Introductionmentioning
confidence: 99%